PREDIABETES: AN ALARM FOR DIABETES? - BAKHYA SHREE. GB; RADHA SARASWATHY (International Journal of Pharma and Bio Sciences, 2016)
Prevalence of prediabetes in India is alarmingly increasing and the percentage of prediabetics exceeds than that of the diabetics. Prediabetes, being asymptomatic and non-diabetic hyperglycemia, could be diagnosed early in order to prevent from advancing to diabetes. Various risk factors such as increased BMI, increased waist-to-hip ratio, gender, sedentary lifestyle and family history for diabetes have been found to be associated with prediabetes. The identification of the predictor for prediabetes among these variables is difficult because the association varies in different ethnic groups based on their lifestyle habits. Thus this review aims at relating the various risk factors and comorbidities associated with prediabetes. It also emphasizes the various possible interventions for the prediabetic individuals in order to prevent them from diabetes.